2020
DOI: 10.1177/1945892420905250
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Sinus Balloon Catheter Dilation Providers Based on Medicare Provider Utilization and Payment Data

Abstract: Background The use of balloon catheter dilation (BCD) to treat chronic rhinosinusitis has increased dramatically since its conception, necessitating further characterization of BCD providers and trends in its usage. Medicare data on BCD providers have made it possible to study recent demographic patterns. There has also been an increase in mid-level providers’ scope of otolaryngologic practice that is not well defined. Objective To better understand BCD adoption by studying volume of BCD procedures as well as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…Physician assistants (PAs) and nurse practitioners (NPs) form a growing advanced practice provider (APP) group and are playing an increasing role in otolaryngology (ENT) practices. 1,2 Many ENT services are provided independently by APPs. Prior to coronavirus disease 2019 emergency responses, NPs practiced with full independence in 22 states and the District of Columbia, while PAs practiced under the supervision of a physician.…”
mentioning
confidence: 99%
“…Physician assistants (PAs) and nurse practitioners (NPs) form a growing advanced practice provider (APP) group and are playing an increasing role in otolaryngology (ENT) practices. 1,2 Many ENT services are provided independently by APPs. Prior to coronavirus disease 2019 emergency responses, NPs practiced with full independence in 22 states and the District of Columbia, while PAs practiced under the supervision of a physician.…”
mentioning
confidence: 99%
“…Using CMS claims data from 2014 and 2015, Munteau et al demonstrated wide differences in BSP performance among otolaryngology subspecialties. 22 Notably, rhinologists and pediatric otolaryngologists recorded the lowest mean number of BSP procedures, whereas facial plastic and general otolaryngologists recorded the highest. 22 In this investigation, we demonstrate that outlier otolaryngologists comprised less than 5% of the study cohort but accounted for greater than 44% of all balloon procedures in the Medicare population.…”
Section: Discussionmentioning
confidence: 97%
“…22 Notably, rhinologists and pediatric otolaryngologists recorded the lowest mean number of BSP procedures, whereas facial plastic and general otolaryngologists recorded the highest. 22 In this investigation, we demonstrate that outlier otolaryngologists comprised less than 5% of the study cohort but accounted for greater than 44% of all balloon procedures in the Medicare population. We also identify characteristics unique to the group of outlier otolaryngologists.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…On the more controversial side of the rhinologic world, a Medicare database analysis by Munteanu et al 2 aimed to better characterize providers performing balloon catheter dilation (BCD) and trends in the usage of balloons for CRS treatment. Expectedly, the authors found that there was a large range in total BCD procedures performed by individual providers (which varied based on several provider characteristics), but quite unexpectedly, they also uncovered that mid-level providers have emerged as a significant population performing these procedures.…”
mentioning
confidence: 99%